Pola Komunikasi Guru di Yayasan Peduli Autisme Bali dalam Meningkatkan Interaksi Sosial Anak Autistik - Claudia Wijaya, Novia; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium; Vol 1 No 1 (2017), 2017)
In dealing with children with special needs in this case autism, of course required appropriate communication patterns so that they would give response and interaction to the statements and questions raised. Autism is a disorder of brain function in children that result in disruption of the child's development. This research was conducted at Yayasan Peduli Autisme Sarwahita Bali. The purpose of this research is to know the proper communication pattern used to children with special needs to improve communication ability and interact them. This study used a qualitative descriptive approach based on post-positivism. Data collection techniques used are by using in-depth interviews, observation, and documentation studies. This study uses the concepts of autism, teacher communication patterns, social interaction, and non-verbal communication concepts. The results of this study indicate that with the right communication pattern will help improve the ability to communicate and interact with children. The communication pattern used in autistic children is not always just one pattern, but the teacher must also be creative in combining the existing communication patterns. Treatment of a child with autism just like any other child, teacher does not spoil a child with autism. Children with autism should also be taught to look for their abilities so that they can be of minimal use for themselves. Appropriate communication patterns can affect the child's social interaction.     Keywords : Autism, Teacher Communication Pattern, Social Interaction